Peran Guru Dan Kepala Sekolah Dalam Implementasi Kurikulum Merdeka Belajar (The Role Of Teachers And School Principals In Implementing The Independent Learning Curiculum) - Iliya Ulva; Uut Istianah; Jasmine Noer Aini; Amalia Rohmatin Nazili; Asih Andriyati (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
Abstract: Education is the main point of support of the progress of a country. Training is an important component of working in HR. HR develops and creates according to the individuals ability to think and think about the design of their own meetings. With changes to educatioanl programs, public authorities want to advance existing educatonal programs, SO that the implementation of educational programs must be able to slowly understand the vision, mission and goals of public schools. Therefore, any changes to the education plan should focus on the conditions experienced in the implementation of the previous education plan. The preparation of this article of educational programs that involve research strategias as writing or writing studies. The free educations program is an educational program with various intracuriculer realizations where the subtance will be more ideal so that student have sufficient opportunities to explore ideas and strengthen skills. The head is the boss and pioneer is continuing to make changes in development at the school. Intructors can contribute cooperatively and actually work with the progress of the schools educational plan to coordinate and design learning materials, books, texts and content.